Association of Inflammatory Cytokines With Non-Alcoholic Fatty Liver Disease - Duan, Yamei; Pan, Xiongfeng; Luo, Jiayou; Xiao, Xiang; Li, Jingya; Bestman, Prince L.; Luo, Miyang (Frontiers in Immunology, 2022)
BACKGROUND: Inflammatory cytokines have been considered to be significant factors contributing to the development and progression of non-alcoholic fatty liver disease (NAFLD). However, the role of inflammatory cytokines in NAFLD remains inconclusive. OBJECTIVE: This study aimed to evaluate the association between inflammatory cytokines and NAFLD. METHODS: PubMed, Web of Science, the Cochrane Library, and EMBASE databases were searched until 31 December 2021 to identify eligible studies that reported the association of inflammatory cytokine with NAFLD and its subtypes. We pooled odds ratios (ORs) and hazard risk (HRs) with 95% confidence intervals (CIs) and conducted heterogeneity tests. Sensitivity analysis and analysis for publication bias were also carried out. RESULTS: The search in the databases identified 51 relevant studies that investigated the association between 19 different inflammatory cytokines and NAFLD based on 36,074 patients and 47,052 controls. The results of the meta-analysis showed significant associations for C-reactive protein (CRP), interleukin-1β (IL-1β), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and intercellular adhesion molecule-1 (ICAM-1) with NAFLD (ORs of 1.41, 1.08, 1.50, 1.15 and 2.17, respectively). In contrast, we observed non-significant associations for interferon-γ (IFN-γ), insulin-like growth factor (IGF-II), interleukin-2 (IL-2), interleukin-4 (IL-4), interleukin-5 (IL-5), interleukin-7 (IL-7), interleukin-8 (IL-8), interleukin-10 (IL-10), interleukin-12 (IL-12), monocyte chemoattractant protein-1(MCP-1), and transforming growth factor-β (TGF-β) with NAFLD. Our results also showed that CRP, IL-1β, and TNF-α were significantly associated with non-alcoholic steatohepatitis (NASH) and hepatic fibrosis. CONCLUSIONS: Our results indicated that increased CRP, IL‐1β, IL-6, TNF‐α, and ICAM-1 concentrations were significantly associated with increased risks of NAFLD. These inflammatory mediators may serve as biomarkers for NAFLD subjects and expect to provide new insights into the aetiology of NAFLD as well as early diagnosis and intervention.